Pipeline pressures and sectoral inflation dynamics - Frank Smets; Joris Tielens; Jan Van Hove (National Bank of Belgium, 2018)
In a production network, shocks originating in individual sectors do not remain confined to individual sectors but permeate through the pricing chain. The notion of "pipeline pressures" alludes to this cascade effect. In this paper we provide a structural definition of pipeline pressures to inflation and use Bayesian techniques to infer their presence from quarterly U.S. data. We document two insights. (i) Due to price stickiness along the supply chain, we show that pipeline pressures take time to materialize which renders them an important source of inflation persistence. (ii) As we trace their origins to 35 disaggregate sectors, pipeline pressures are documented to be a key source of headline/disaggregated inflation volatility. Finally, we contrast our results to the dynamic factor literature which has traditionally interpreted the comovement of price indices arising from pipeline pressures as aggregate shocks. Our results highlight the role of sectoral shocks - joint with the production architecture - to understand the micro origins of disaggregate/headline inflation persistence/volatility.
Keywords: E31; E32; D85; O51; 330; Pipeline pressures; Input-output linkages; Propagation